Visuo-spatial imagery in dreams of congenitally and early blind: a systematic review - Ilic, Katarina; Bertani, Rita; Lapteva, Neda; Drakatos, Panagis; Delogu, Alessio; Raheel, Kausar; Soteriou, Matthew; Mutti, Carlotta; Steier, Joerg; Carmichael, David W.; Goadsby, Peter J.; Ockelford, Adam; et al. (Frontiers in Integrative Neuroscience, 2023)
Background The presence of visual imagery in dreams of congenitally blind people has long been a matter of substantial controversy. We set to systematically review body of published work on the presence and nature of oneiric visuo-spatial impressions in congenitally and early blind subjects across different areas of research, from experimental psychology, functional neuroimaging, sensory substitution, and sleep research. Methods Relevant studies were identified using the following databases: EMBASE, MEDLINE and PsychINFO. Results Studies using diverse imaging techniques and sensory substitution devices broadly suggest that the “blind” occipital cortex may be able to integrate non-visual sensory inputs, and thus possibly also generate visuo-spatial impressions. Visual impressions have also been reported by blind subjects who had near-death or out-of-body experiences. Conclusion Deciphering the mechanistic nature of these visual impression could open new possibility in utilization of neuroplasticity and its potential role for treatment of neurodisability.